An environmentally tolerant, highly stable, cellulose nanofiber-reinforced, conductive hydrogel multifunctional sensor. (15th May 2022) - Li, Miao; Chen, Dong; Sun, Xia; Xu, Zesheng; Yang, Yutong; Song, Yongming; Jiang, Feng
Abstract: The application of flexible multifunctional sensors based on conductive hydrogels in human health detection has been widely studied. Herein, a facile one-pot method is proposed to prepare ionic conductive hydrogels by dissolving polyvinyl alcohol (PVA), cellulose nanofiber (CNF), and aluminum chloride hexahydrate (AlCl3 ·6H2 O) in a dimethyl sulfoxide (DMSO)/water binary solvent. The resulting ionically-conductive organohydrogels have high stretchability (up to 696%), fast response (130 ms), wide operating temperature (−50 °C to 50 °C), and long-term stability (30 days). The hydrogel sensor exhibits excellent signal sensing capability (human motion and sound detection signals) and cycling stability (1000 cycles) under extreme temperature and long-term storage conditions. Notably, the organohydrogel displays high sensitivity to both compressive deformation and temperature, resulting in multifunctional sensing performance. This work provides a viable approach for the long-term use of hydrogels as wearable devices in extreme environments and daily life. Graphical abstract: Physically cross-linked organohydrogels with good stretchability, environmental tolerance, and long-term stability were prepared from cellulose nanofibers for multifunctional sensors. Unlabelled Image